Chronic heart failure: syndrome or disease? - V. V. Kalyuzhin; A. T. Teplyakov; G. E. Chernogoryuk; E. V. Kalyuzhina; I. D. Bespalova; N. N. Terentyeva; I. K. Livshits; V. L. Ostanko; O. F. Sibireva; N. Yu. Chasovskikh (Бюллетень сибирской медицины)
The authors of the study analyze various definitions of chronic heart failure (CHF). CHF, having many faces, despite the consensus concerning the paradigm of its pathogenesis, is given different definitions, using both the syndromic and nosological approaches. Most authors share a view of CHF as the final stage (outcome or complication) of many diseases in which there is impairment of ventricular filling or ejection of blood, i.e. as a syndrome, and not an independent nosological form. Nevertheless, at the beginning of the XXI century leading Russian specialists in heart failure presented a reasoned point of view on CHF not only as the final stage of the cardiovascular continuum, complicating the course of a disease of the cardiovascular system, but also as an independent nosological form. This approach, which contradicts the standard rules for the formulation of the final clinical and pathological diagnoses, as well as the agreed positions of the International Statistical Classification of Diseases and Related Health Problems, has been the subject of reasonable criticism. Since the identification of the underlying cause of heart failure is crucial for therapeutic reasons, the only correct view is that of CHF as a syndrome, the detailed description of which in clinical diagnosis is an important intranosological characteristic that allows building the most effective differentiated therapy and accurately determining the prognosis of the disease.